Pengendalian Motor Listrik Dari Jarak Jauh Dengan Menggunakan Software Zelio Soft 2 Dan Wifi - Janeer E.T. Pioh; Lily S. Patras; Fielman Lisi (Universitas Sam Ratulangi, 2016)
Abstract – The development of increasingly rapid automation system cannot be separated from the development of technology in the field of electricity and control. Development of electrical equipment that can be controlled remotely so that the processing time can be shortened. Smart relay is a control device that have additional control functions that are not owned by the conventional control devices in general. Electric Motor Control Remotely Using Zelio Soft 2 Software and Wifi, programmed using ladder diagram programming language. Application in the process of controlling the distance, such as: 3-phase induction motor control and control of the pump motor in the process of filling the tank of water from the source to the tank. Keywords – Electric Motors, Remote Controls, Smart relay, Zelio Soft 2. Abstrak – Perkembangan sistem otomasi yang semakin pesat tidak lepas dari berkembangnya teknologi dalam bidang kelistrikan dan pengontrolan. Pengembangan peralatan listrik yang dapat dikontrol dari jarak jauh sehingga waktu pengerjaan dapat dipersingkat. Smart relay adalah sebuah alat kontrol yang memiliki fungsi kontrol tambahan yang tidak dimiliki alat pengendali konvensional pada umumnya. Pengendalian Motor Listrik dari Jarak Jauh dengan Menggunakan Software Zelio Soft 2 dan Wifi, diprogram menggunakan bahasa pemrograman ladder diagram. Aplikasinya pada proses pengontrolan jarak jauh, yaitu: pengontrolan motor induksi 3 fasa dan pengontrolan motor pompa pada proses pengisian air dari tangki sumber ke bak penampungan. Kata kunci – Kontrol Jarak Jauh, Motor Listrik, Smart relay, Zelio Soft 2.